Drug interactions in female oncologic inpatients: differences among databases - Patricia Moriel; Jorge Augusto Siqueira; Renata Cavalcanti Carnevale; Caroline de Godoi Rezende Costa; Aline Aparecida da Cruz; Nice Maria Oliveira da Silva; Adélia Corina Bernardes; Roberta Paro Carvalho; Priscila Gava Mazzola (São Paulo State University (UNESP), 2013)
The aim of the present study was to quantify drug interactions in prescriptions for women undergoing supportive therapy in an oncology setting at a women's hospital in Brazil and compare the information provided by different databases regarding these drug interactions. A convenience sample was selected of prescriptions for patients diagnosed with breast or gynecological tumors hospitalized in the clinical oncology and surgery wards from April to June 2009. DRUGDEX/Micromedex (Thomson Micromedex) was the main database used for the identification of drug interactions and was compared with two other databases: Drugs.com and Lexicomp. The search was performed by inputting all drug combinations found in the prescriptions in Micromedex and Drugs.com. All interactions identified and classified by Micromedex and/or Drugs.com as of major severity were then checked in Lexicomp. A total of 152 interactions were identified by Micromedex (61 major, 69 moderate and 22 minor). In Drugs.com, 614 interactions were identified (85 major, 464 moderate and 65 minor). Forty-four were classified as major drug interactions in at least one of the databases: 30 in Micromedex, 26 in Drugs. com and 14 in Lexicomp. The present findings reveal discrepancies among the three databases analyzed. Thus, standardization should be proposed. Moreover, both the pharmacist and multidisciplinary team should perform a critical analysis of prescriptions to promote safe practices in the use of medications and minimize potential complications caused by drug interactions.